UJI EFEK ANTIPIRETIK DAUN SENDUDUK (Melastoma malabathricum L.) PADA TIKUS PUTIH JANTAN (Rattus Norvegicus) - Evi Depiana Gultom; Herti Ayu N Zebua; Robiatun Rambe (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
The antipyretic effect of flavonoid in senduduk leaf (Melastoma malabathricum L.) is one of the traditional medicines that people used. The goal of this study is to determine the antipyretic effect of the extract of Senduduk leaf (Melastoma malabathricum L.) in male white mice and compare it to paracetamol. The design of this experimental study was a post-test only controlled group design. Twenty-five Wistar furrow mice, aged two months and weighing 200 grams, were utilized as animal models. The mice were divided into five groups, one of which was the negative control group (2 ml water), First dosage of Senduduk leaf extract (100 mg/200 g body weight mice), second dose of the extract (200 mg/200 g body weight mice), and third dose of the extract (300 mg/200 g body weight mice). Temperature measurements were taken before and after the DPT vaccination was administered to mice, and every 30 minutes post treatment until 150 minutes. The result after observing treatment at 30 minutes for dose I (37.930C), dose II (37.760C), and dose III (37.450C). The results at 150 minutes for dose I (37,470C), for dose II (37,150C), and for dose III (36.880C). The result of the research was to analyzed using the one way ANOVA test. The results of statistical observations using the one way ANOVA method showed the significant value was p < 0.05 (0.000). This indicates there are differences from each treatment in antipyretic testing. If continued with the Tukey test, a significant value of p> 0.05 (0.9480), the research concluded that there is no difference in terms of antipyretic testing at a dose of 300mg/KgBW compared to paracetamol. The research concluded is the EEDS at a dose of 300mg/KgBW has the best antipyretic properties compared to paracetamol.